2022
DOI: 10.24093/awej/vol13no4.19
|View full text |Cite
|
Sign up to set email alerts
|

English Majors’ Perceptions of Chinese-English Translation Learning and Translation Competence

Abstract: Translation is an indispensable language activity and communication method. Translation from Chinese to foreign languages, especially English, is significant to tell Chinese stories well, growing into an urgent issue in China. While cultivating translation talents is crucial, translation competence is a complicated system consisting of various sub competences. To improve English majors’ Chinese-English (C-E) translation competence, it is necessary to first investigate their perceptions of C-E translation learn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Fourth, disciplines such as corpus linguistics and English for Special Purposes offer new sources of inspiration for teaching translation. Finally, new methods and technologies in the digital age play an important role in teaching translation in China (Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, disciplines such as corpus linguistics and English for Special Purposes offer new sources of inspiration for teaching translation. Finally, new methods and technologies in the digital age play an important role in teaching translation in China (Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current situation, the problem is that not many teachers know the MTI program very well, and what is more serious is that these teachers lack a certain practical experience in translation due to their long-term heavy teaching duties [12]. Literature [13] collected data by distributing questionnaires to English translation master's students, and the survey showed that information about English majors' cognitive information about Chinese-English translation learning and translation competence is crucial for improving translation competence. Literature [14] explored using a projectbased flipped learning model in a business English translation course, which involves learning, teaching and assessment aspects.…”
Section: Introductionmentioning
confidence: 99%